PANDEMIC IMPACT OF COVID-19 ON THE HEALTH OF SYARIAH BANKS - Sukma Wijayanti; Zaenal Afifi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the comparison of the health level of banks syariah before and after the Covid-19 pandemic using the measurement method stipulated in the provisions of Bank Indonesia PBI Number 13/1 / PBI / 2011 concerning Bank Health Assessment using the RGEC method. The assessment factors in the RGEC method are risk profile factors, good corporate governance (GCG) factors, profitability factors, and capital factors. The object of this research is all banks syariah companies listed on the Bursa Efek Indonesia from 2017 to 2019. The sampling technique in this study uses a census or population. The analysis technique in this research is descriptive quantitative. The results of this study indicate that banks syariah that were included in the healthy category before the Covid-19 pandemic were Bank Panin Dubai Syariah and banks syariah that were included in the very healthy category were Bank Rakyat Indonesia Syariah and Bank Tabungan Pensiun Syariah. At the time of the Covid-19 pandemic, the three bank syariah were in the very healthy category. Overall, banks syariah are able to grow well even in the COVID-19 pandemic situation.